Understanding online impulse buying in China’s live ecommerce: the role of key opinion leaders and perceived trust - Cai, Shuang; Ambad, Sylvia Nabila Azwa (Universiti Teknologi MARA, Perlis, 2025)
In the current environment where live streaming e-commerce is booming, creating key opinion leaders has become a very common and effective marketing strategy. Perceived trust, an important antecedent factor influencing consumers buying behaviour, deserves more exploration. This study examines the impact of key opinion leaders on the live streaming e-commerce industry in China, focusing on the interaction and expertise dimensions of key opinion leaders and their influence on consumers’ impulse buying behaviour. A quantitative research method was adopted, and data were collected through a questionnaire survey on Questionnaire Star forms. The survey participants were 203 users of Douyin, Kuaishou, and Taobao Live aged between 18 and 34, currently residing in Guangxi, Jiangxi, and Anhui provinces in China. The existing measurement items were adjusted accordingly for the live streaming e-commerce industry, and the data were analysed using SmartPLS 4.0. The results show that only expertise has a direct effect on perceived trust, which in turn mediates the relationship between the expertise of key opinion leaders and consumers’ online impulse buying behaviours. In contrast, the interaction dimension of key opinion leaders does not have a direct or indirect effect on online impulse buying behaviour. The findings of this study provide valuable insights for the live streaming ecommerce industry, which is on the rise in this digital age.